Deletion of ESX-3 and ESX-4 secretion systems in Mycobacterium abscessus results in highly impaired pathogenicity - Wassim Daher; Vincent Le Moigne; Yara Tasrini; Shweta Parmar; Danielle L. Sexton; John Jairo Aguilera-Correa; Valentin Berdal; Elitza I. Tocheva; Jean-Louis Herrmann; Laurent Kremer (Communications Biology)
Abstract Type VII secretion systems participate in protein export, virulence, conjugation, and metabolic regulation. Five subtypes (ESX-1 to ESX-5) exist, each with specific roles and well-characterized secretion profiles in various mycobacterial species. Mycobacterium abscessus, encodes only ESX-3 and ESX-4. Here, single and double M. abscessus mutants lacking the main ATPases EccC3 and EccC4 were used to define ESX-3 and ESX-4 contributions to substrate secretion and virulence. Our results demonstrate that EsxG/H secretion depends entirely on ESX-3, whereas both ESX-3 and ESX-4 secrete EsxU/T. Furthermore, two newly identified PE/PPE substrates (MAB_0046/MAB_0047) require ESX-3 for secretion. Functional complementation restored secretion and revealed subpolar localization of these systems. Macrophage infections showed that ESX-3 and ESX-4 contribute to bacterial internalization, phagosomal escape, and intracellular survival. In mice, infections with eccC3- and/or eccC4-deletion mutants resulted in complete survival and reduced bacterial loads in the lungs. These findings demonstrate that both ESX systems drive M. abscessus pathogenicity.